A Simulation of the Process of High Speed Milling of Titanium Alloy VT-1-0 in DEFORM-3D - Sherov, Karibek; Tussupova, Sayagul; Kuzminova, Nadezhda; Makhmudov, Lutfiddin; Mardonov, Bakhtiyor; Ainabekova, Saule; Abdugaliyeva, Gulnur; Kokayeva, Gulnara; Mendalieva, Saule; Kardassinov, Sayat (Engineering, Technology & Applied Science Research, 2025)
This study examined the High-Speed Milling (HSM) process of titanium alloy VT-1-0 using the Deform-3D simulation software. The simulation modeled the HSM operation and analyzed the distribution of temperature and strain in the cutting zone. The results indicated that deformation primarily occurred at the tool-workpiece interface and propagated more intensely into the sheared material at an angle of approximately 45°. Increasing the spindle speed of the end mill led to greater strain values in the cutting zone. Due to the low thermal conductivity of titanium, high temperatures-exceeding 1500 °C were localized at the tool-workpiece contact area. This concentration of heat, coupled with its slow dissipation throughout the workpiece, negatively affected the surface quality and tool life. Additionally, increasing both the feed rate and cutting speed resulted in higher temperatures and intensified friction at the interface.. The findings of this simulation provided valuable insights for optimizing the cutting parameters and better understanding the machinability of titanium under HSM conditions.